A high plane of nutrition during early life alters the hypothalamic transcriptome of heifer calves - José M. Sánchez (Nature Portfolio, 2021)
Abstract The aim was to examine the effect of rapid body weight gain during early calfhood consistent with earlier sexual development on the transcriptional profile of the hypothalamus. Angus X Holstein–Friesian heifer calves (19 ± 5 days of age) were offered a high (HI, n = 14) or moderate (MOD, n = 15) plane of nutrition from 3 to 21 weeks of age to achieve a growth rate of 1.2 kg/d and 0.5 kg/d, respectively. Following euthanasia at 21 weeks, the arcuate nucleus (ARC) region was separated from the remainder of the hypothalamus and both were subjected to RNA-Seq. HI calves exhibited altered expression of 80 and 39 transcripts in the ARC and the remaining hypothalamus, respectively (P < 0.05) including downregulation of AGRP and NPY and upregulation of POMC, previously implicated in precocious sexual development. Stress-signaling pathways were amongst the most highly dysregulated. Organ morphology, reproductive system development and function, and developmental disorder were amongst the networks derived from differentially expressed genes (DEGs) in the ARC. Gene co-expression analysis revealed DEGs within the ARC (POMC, CBLN2, CHGA) and hypothalamus (PENK) as hub genes. In conclusion, enhanced nutrition during early calfhood alters the biochemical regulation of the hypothalamus consistent with advanced sexual development in the prepubertal heifer.